PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN THE EVITEL HOTEL BATAM - GRACE INGELYN; REALIZE . (JURNAL ILMIAH MAKSITEK, 2020)
The development of tourism in the city of Batam has increased very rapidly. There is more competition in service companiesso that certain strategies are needed to survive in the market. Companies must maximize customer satisfaction in order tomaintain the survival of the company. In achieving customer satisfaction, the company must pay attention to two variables,that is promotion and service quality. In this study, to determine and analyze the effect of promotion and service quality oncustomer satisfaction at The Evitel Hotel Batam. At The Evitel Hotel Batam, the promotion is still lacking due to the lack ofpromoting the company through social media so that less consumers from outside Indonesia in using hotel services and alsothe lack of giving promos like discounts. In service quality, the lack of provided such as unfriendly staff and lack ofcommunicative between consumers at the cashier. This study has a population of 335 consumers. The sample used was apurposive sampling technique, in calculating the number of samples using the slovin formula with a sample of 182consumers. Data collection techniques in this study using a questionnaire. The data processing method in this study usesSPSS 25. Based on the test results, the promotion and quality of service simultaneously has a positive and significantinfluence on customer satisfaction.